2013
DOI: 10.1177/0266242613484777
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneur ambidexterity: A study of entrepreneur behaviours and competencies in growth-oriented small and medium-sized enterprises

Abstract: This article uses the sociological method of structured observation to explore the every day behaviour of entrepreneurs from an exploration-exploitation perspective. Six entrepreneurs leading successful growth-oriented businesses were observed for a four-day period and 2305 ‘units of action’ performed by the entrepreneurs were recorded. Six behavioural patterns that allowed them, their management team or the organisation as a whole to pursue ambidexterity were identified. In contrast with the existing high-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 51 publications
5
133
0
12
Order By: Relevance
“…Because ambidexterity has typically been studied in the context of large, often multi-unit firms, to date there is scant research of ambidexterity in young entrepreneurial firms. There have been some studies that have investigated ambidexterity within SMEs (Lubatkin et al 2006, Fernhaber andVoss and Voss 2013;Abebe and Angriawan 2014;Kim and Huh 2015a, b), but only two studies that have a similar early stage focus as the present study (Frigotto et al 2014;Volery et al 2015). The present study enhances the literature's understanding of the role of ambidexterity in young entrepreneurial firms, because it targets firms that are less than 10 years old with less than 50 employees.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Because ambidexterity has typically been studied in the context of large, often multi-unit firms, to date there is scant research of ambidexterity in young entrepreneurial firms. There have been some studies that have investigated ambidexterity within SMEs (Lubatkin et al 2006, Fernhaber andVoss and Voss 2013;Abebe and Angriawan 2014;Kim and Huh 2015a, b), but only two studies that have a similar early stage focus as the present study (Frigotto et al 2014;Volery et al 2015). The present study enhances the literature's understanding of the role of ambidexterity in young entrepreneurial firms, because it targets firms that are less than 10 years old with less than 50 employees.…”
Section: Introductionmentioning
confidence: 69%
“…Research on SMEs has indicated that the top management team has an important role in managing levels of exploration or exploitation (Lubatkin et al 2006;Volery et al 2015;Parida and Örtqvist 2015). Top management in SMEs, as opposed to their counterparts in large organizations, often participates in implementing a firm's strategies day-by-day.…”
Section: Literature Reiviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Boyatzis (1983), establece una tipología de las competencias basada en un marco teórico de estilos de aprendizaje y la teoría del aprendizaje experiencial, en lugar del rendimiento en el trabajo o rasgo de personalidad, de lo cual deriva la necesidad del desarrollo del concepto a partir de las habilidades de aprendizaje de un dominio específico y rica en conocimientos; dominio de una transacción integrada entre la persona y el medio ambiente; dominio desarrollado por la práctica En general, las competencias se han definido como componentes combinados e integrados de conocimientos, habilidades y actitudes. Como tal las competencias son cambiables, se las pueden aprender y ser alcanzables a través de la experiencia, entrenamiento o coaching (Man et al, 2002;Volery et al, 2015;Wagener et al, 2010). Las habilidades que un empresario necesita poseer para ejecutar un negocio exitoso ha sido conceptualizado tanto de una manera global como específica.…”
Section: Competenciasunclassified